Safeguarding the catalytic activity and stability of polyaniline chitosan silver nanocomposite bound beta-galactosidase against product inhibitors and structurally related compound - Maryam Khan; Qayyum Husain (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
In this study, an attempt has been made to evaluate the effect of products of β-galactosidase (βGS) catalyzed reaction i.e. glucose and galactose and their structurally related compound vitamin C (VC) on the catalytic activity of native and PANI-CS-NC and PANI-CS-Ag-NC adsorbed βGS. Results indicated a decline in catalytic activity of soluble enzyme in the presence of all investigated compounds. The order of inhibition was found to be VC < glucose < galactose. However, the immobilized preparations were found more resistant to inactivation caused by the added compounds. About 48% activity was retained by PANI-CS-Ag-NC-βGS in the presence of galactose (5%, w/v), while the native enzyme exhibited only 18% of its original activity. A significant decrease in absorbance and fluorescence intensity was evaluated in soluble enzyme incubated in the presence of all investigated compounds. Three-dimensional fluorescence graphs, CD and FT-IR spectroscopic studies illustrated noteworthy conformational changes in the secondary structure and microenvironment of the soluble enzyme in the presence of VC and tested sugars. These results suggest that both PANI-CS-NC and PANI-CS-Ag-NC bound βGS are more resistant to the exposure caused by the higher concentration of added glucose, galactose, and VC and, therefore, can be effectively utilized for the production of a hassle-free lactose nano-biosensor.